Haemoperitoneum: a rare consequence of medial migration of K wire - Bibekananda Mahapatra, Bibekananda; Deolekar, Sandesh; Murali, Sridevi; Chheda, Karna; Khan, Naseem (International Journal of Research in Medical Sciences, 2017)
Upper femoral corrective osteotomy with K wire stabilization has been recognized as a common method in the treatment of tuberculosis of hip in the field of orthopedics surgery. But here we report an unusual surgical complication due to penetration by an implant through a bone with osteomyelitis due to tuberculosis, the case of a 20-year-old male who presented with Hemoperitoneum, a general surgical complication which occurred due to the rupture of a retro-peritoneal hematoma formed by the intra-pelvic medial migration of the K wire.